Association between traumatic stress load, psychopathology, and cognition in the Philadelphia Neurodevelopmental Cohort. Issue 2 (15th April 2018) - Barzilay, Ran; Calkins, Monica E.; Moore, Tyler M.; Wolf, Daniel H.; Satterthwaite, Theodore D.; Cobb Scott, J.; Jones, Jason D.; Benton, Tami D.; Gur, Ruben C.; Gur, Raquel E.
Abstract: Background: Traumatic stressors during childhood and adolescence are associated with psychopathology, mostly studied in the context of post-traumatic stress disorder (PTSD) and depression. We investigated broader associations of traumatic stress exposure with psychopathology and cognition in a youth community sample. Methods: The Philadelphia Neurodevelopmental Cohort ( N = 9498) is an investigation of clinical and neurobehavioral phenotypes in a diverse (56% Caucasian, 33% African American, 11% other) US youth community population (aged 8–21). Participants were ascertained through children's hospital pediatric (not psychiatric) healthcare network in 2009–2011. Structured psychiatric evaluation included screening for lifetime exposure to traumatic stressors, and a neurocognitive battery was administered. Results: Exposure rate to traumatic stressful events was high (none, N = 5204; one, N = 2182; two, N = 1092; three or more, N = 830). Higher stress load was associated with increased psychopathology across all clinical domains evaluated: mood/anxiety (standardized β = .378); psychosis spectrum ( β = .360); externalizing behaviors ( β = .311); and fear ( β = .256) (controlling for covariates, all p < 0.001). Associations remained significant controlling for lifetime PTSD and depression. Exposure to high-stress load was robustly associated with suicidal ideation and cannabis use (odds ratio compared with non-exposed 5.3 and 3.2, respectively, both p < 0.001). Among youths who experienced traumatic stress ( N = 4104), history of assaultive trauma was associated with greater psychopathology and, in males, vulnerability to psychosis and externalizing symptoms. Stress load was negatively associated with performance on executive functioning, complex reasoning, and social cognition. Conclusions: Traumatic stress exposure in community non-psychiatric help-seeking youth is substantial, and is associated with more severe psychopathology and neurocognitive deficits across domains, beyond PTSD and depression.